QUALITY ASSURANCE MECHANISMS FOR QUALITY RESEARCH OUTPUTS OF STEM LECTURERS IN UNIVERSITIES IN RIVERS STATE: ISSUES ON PLAGIARISM (UNIZIK Journal of Educational Management and Policy, 2024)
This study was aimed at investigating the quality assurance mechanisms for managing the research outputs of STEM lecturers in universities in Rivers State. The study is a descriptive survey with a population of 993 lecturers and a sample size of 160 STEM lecturers obtained through purposive and simple random sampling techniques. The instrument used for data collection was a self-structured questionnaire tagged “Quality Assurance Mechanisms for Research Outputs Questionnaire” (QAMROQ). The instrument was designed after the modified 4-point Likert rating scale of Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD) with numerical values of 4, 3, 2, and 1 respectively. The instrument was face validated by two experts. A reliability coefficient of 0.80 was established through Pearson Product Moment Correlation coefficient. Data collected was analysed using mean scores. While a mean value of 2.50 was used as benchmark for the interpretation of results. The result revealed among others the institutional mechanisms for managing STEM lecturers’ research outputs as self-review, peer review, external quality assessment, and review panel. The technological mechanisms were identified as Computer-Based Plagiarism Detector, Turnitin, Copy-Catch-Gold, Quetext, and Word-Check. Based on the findings, it was recommended among others that Deans of faculties should ensure the effective use of quality assurance mechanisms in producing quality research outputs in their faculties
Keywords: quality assurance mechanisms, plagiarism, research outputs, STEM lecturers